2016
DOI: 10.1021/acs.est.6b02147
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stage Exposure to BDE-47 Causes Adverse Effects on Reproductive Success and Sexual Differentiation in Fathead Minnows (Pimephales promelas)

Abstract: 2,2',4,4'-Tetrabromodiphenyl ether (BDE-47), a compound manufactured for use as a flame retardant, is a ubiquitous environmental contaminant and suspected endocrine disruptor. Though several studies have explored the reproductive effects of BDE-47 in adult fish, there is a paucity of data regarding the reproductive effects of early life stage exposure. The goal of this study was to assess the reproductive effects of early life stage BDE-47 exposure in fathead minnows (Pimephales promelas). To achieve this, min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The early life stage of zebrafish (Danio rerio) is widely used as a model to characterize the toxicities of pollutants (Fu et al 2013;Li et al 2017; Thornton et al 2016) because the early life stage of fish is considered the most sensitive to environmental stressors (Embry et al 2010;Villeneuve et al 2014;Volz et al 2011). In addition, embryonic zebrafish have been proposed as a cost-effective platform to assess the bioaccumulations of pollutants (Sanz-Landaluze et al 2015;Sun et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The early life stage of zebrafish (Danio rerio) is widely used as a model to characterize the toxicities of pollutants (Fu et al 2013;Li et al 2017; Thornton et al 2016) because the early life stage of fish is considered the most sensitive to environmental stressors (Embry et al 2010;Villeneuve et al 2014;Volz et al 2011). In addition, embryonic zebrafish have been proposed as a cost-effective platform to assess the bioaccumulations of pollutants (Sanz-Landaluze et al 2015;Sun et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were seen after early-life exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) in fathead minnows ( Pimephales promelas ). Those authors regarded altered estrogenic activity of BDE-47 as a cause (Thornton et al, 2016). During medaka embryogenesis, sex hormones direct the developmental form of estrogens thereby mediating development of female sex organs and their functional characteristics (Matsuda, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of PBDEs were as high as 29 μg/L in polluted water and commonly detected at levels of μg/g to mg/g dry weight in biota samples. Therefore, the long-term health consequences of PBDEs remain non-negligible. The adverse effects of PBDEs are diverse and complicated, characterized by endocrine thyroid disruption, reproduction toxicity, and visual impairment. , Great research concerns are focused on the neurotoxicity of PBDEs, especially at the early stages of life . Multiple cohort studies reported the relationships between PBDEs and depressive symptoms, and significant positive associations were observed, especially with 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47). , It is of note that there is a consistent pattern between more sleep problems and higher BDE-47 serum level at 4 year old children in a birth cohort study of Shanghai-Minhang, China .…”
Section: Introductionmentioning
confidence: 99%